Oxidation of P700 in Photosystem I Is Essential for the Growth of Cyanobacteria . Issue 3 (9th September 2016) - Shimakawa, Ginga; Shaku, Keiichiro; Miyake, Chikahiro
Abstract : Oxidation of P700 in photosystem I prevents the photoinhibition of photosystem I to enable cyanobacteria to grow under ambient [CO2 ]. Abstract: The photoinhibition of photosystem I (PSI) is lethal to oxygenic phototrophs. Nevertheless, it is unclear how photodamage occurs or how oxygenic phototrophs prevent it. Here, we provide evidence that keeping P700 (the reaction center chlorophyll in PSI) oxidized protects PSI. Previous studies have suggested that PSI photoinhibition does not occur in the two model cyanobacteria, Synechocystis sp. PCC 6803 and Synechococcus elongatus PCC 7942, when photosynthetic CO2 fixation was suppressed under low CO2 partial pressure even in mutants deficient in flavodiiron protein (FLV), which mediates alternative electron flow. The lack of FLV in Synechococcus sp. PCC 7002 (S. 7002 ), however, is linked directly to reduced growth and PSI photodamage under CO2 -limiting conditions. Unlike Synechocystis sp. PCC 6803 and S. elongatus PCC 7942, S. 7002 reduced P700 during CO2 -limited illumination in the absence of FLV, resulting in decreases in both PSI and photosynthetic activities. Even at normal air CO2 concentration, the growth of S. 7002 mutant was retarded relative to that of the wild type. Therefore, P700 oxidation is essential for protecting PSI against photoinhibition. Here, we present various strategies to alleviate PSI photoinhibition in cyanobacteria.